(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
This study aims to analyze the effectiveness of the JPN function in resolving inter-governmental institutional disputes through mediation from the perspectives of Access to Justice and Good Governance. This research employs a normative juridical method with a descriptive-analytical design. The study uses statutory, conceptual, and case approaches by examining relevant regulations, legal doctrines, academic literature, and other legal materials related to the authority and implementation of JPN functions. The collected legal materials are analyzed qualitatively through legal interpretation and deductive reasoning to evaluate the effectiveness of JPN mediation. The findings indicate that JPN has a strategic role not only as a legal representative of the state but also as a facilitator of non-litigation dispute resolution. The effectiveness of JPN mediation is influenced by regulatory support, professional capacity, institutional coordination, and the willingness of government institutions to utilize alternative dispute resolution mechanisms. This study contributes theoretically by integrating legal effectiveness theory with Access to Justice and Good Governance perspectives, while practically providing recommendations for strengthening JPN capacity and improving government dispute resolution mechanisms. The study concludes that optimizing the role of JPN in mediation can support a more effective, accountable, and justice-oriented government dispute resolution system.